2022
DOI: 10.3389/fimmu.2022.943389
|View full text |Cite
|
Sign up to set email alerts
|

A novel tumor mutational burden-based risk model predicts prognosis and correlates with immune infiltration in ovarian cancer

Abstract: Tumor mutational burden (TMB) has been reported to determine the response to immunotherapy, thus affecting the patient’s prognosis in many cancers. However, it is unclear whether TMB or TMB-related signature could be used as prognostic indicators for ovarian cancer (OC), as its potential association with immune infiltration remains poorly understood. Therefore, this study aimed to develop a novel TMB-related risk model (TMBrisk) to predict the prognosis of OC patients on the basis of exploring TMB-related gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…According to our results, patients with EC (Table 2) and mucinous carcinoma (Supplementary Table 3) tended to have a higher ratio of TMB-high values. Zhu et al also documented that the TMB of mucinous tumors in their study was higher than that of HGSC and LGSC (56). However, limited by the sample sizes in our study, more patient data in a larger cohort will be collected to verify this conclusion.…”
Section: B Amentioning
confidence: 52%
See 1 more Smart Citation
“…According to our results, patients with EC (Table 2) and mucinous carcinoma (Supplementary Table 3) tended to have a higher ratio of TMB-high values. Zhu et al also documented that the TMB of mucinous tumors in their study was higher than that of HGSC and LGSC (56). However, limited by the sample sizes in our study, more patient data in a larger cohort will be collected to verify this conclusion.…”
Section: B Amentioning
confidence: 52%
“…Zhu et al. also documented that the TMB of mucinous tumors in their study was higher than that of HGSC and LGSC ( 56 ). However, limited by the sample sizes in our study, more patient data in a larger cohort will be collected to verify this conclusion.…”
Section: Discussionmentioning
confidence: 80%
“…TMB can determine the response of immunotherapy, thus affecting the prognosis of many cancer patients 16 . We conducted mutation analysis on HCC samples of two subgroups and the results revealed that TP53 and CTNNB represented a higher genetic mutation frequency than the low‐risk group (Figure 6A,B).…”
Section: Resultsmentioning
confidence: 99%
“…OC is a primary gynecologic malignancies tumor, and most OC patients were diagnosed at an advanced stage that has a high ability to damage surrounding tissues, so the prognosis is poor among OC patients. [29] Accordingly, exploring effective biomarkers is crucial for OC patients. In this research, circMFN2 regulated CUL4B to promote OC progression via sponging miR-198, which is expected to provide a latent treatment strategy for patients with OC.…”
Section: Discussionmentioning
confidence: 99%